Women Leading the Way - Laura S.H. Holgate; Inna Pletukhina; Michelle Reichert; Şebnem Udum; Ashley A Humphrey (International Journal of Nuclear Security, 2022)
As a feature of this issue, we asked some of the most notable women in the nuclear security profession to share their stories. Knowing that other women overcame circumstances that women still face instills hope, shows leadership, and provides mentorship to us all.